Directional defrosting on partially suspended surfaces of varying hydrophobicity under angular influences - Lai, Jemison Weng Keat (Nanyang Technological University, 2020)
The undesirable accumulation of frost on surfaces is a persistent problem that has detrimental implications to numerous industries such as aviation, maritime and heat transfer applications. While preventive and active solutions to alleviate the impact of frosting has been progressively studied upon over the years, this final year project aims to expand upon the current research to examine the effects on the efficiency and effectiveness of directional defrosting under a range of inclined angular orientations through utilizing liquid runoff and delamination effects to improve the defrost, and in extension, the de-wetting process. This report encompasses the details of the planning and fabrication of the test rig, the design of the experiment, results gathered and discussion of the obtained findings. Through the course of this project, it was discovered that a hydrophilic surface would produce the quickest defrost time required at the expense of having the highest water retention on the material surface. A Super-hydrophobic surface on the contrary would require the longest defrosting time but would result in a surface that is mostly devoid of retained liquid. Further analysis deduces that a super-hydrophobic surface would thus in turn, require less extra energy input and overall time required for the complete de-wetting over that of the hydrophilic surface.It is thus recommended to utilize a hydrophilic surface for applications that demand rapid defrosting with no interest in water retention whilst a super-hydrophobic surface is to be used for applications that necessitate the complete de-wetting of the critical surfaces,with a limited or more efficient energy input.It is also identified that the angular orientation significantly impacts the performance efficiency of a super-hydrophobic surface in defrost and de-wetting applications due to contributions to its unique delamination phenomenon. It was observed that a steeper, or inverted incline would produce more favourable results in terms of maximizing defrost speed and minimizing surface liquid retention. The angular displacement however, is not a factor to that of hydrophobic and hydrophilic surfaces, in which the effects of surface morphology takes precedence over that of the gravitational effects that benefit from the angular changes introduced.